2013
DOI: 10.1111/1365-2656.12186
|View full text |Cite
|
Sign up to set email alerts
|

Inducible offences affect predator–prey interactions and life‐history plasticity in both predators and prey

Abstract: 1. Phenotypic plasticity can have strong impacts on predator-prey interactions. Although much work has examined the effects of inducible defences, less understood is how inducible offences in predators affect predator-prey interactions and predator and prey phenotypes. 2. Here, we examine the impacts of an inducible offence on the interactions and life histories of a cohort of predatory Hynobius retardatus salamander larvae and their prey, Rana pirica tadpoles. We examined larval (duration, survival) and post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Trait variation in response to present environmental cues (e.g. development of anti-predator morphologies or nutrient stress) frequently affects interactions between diverse taxa such as plants and herbivores (terHorst & Lau 2012), protists (DeLong, Hanley & Vasseur 2013), invertebrates (Hoverman & Relyea 2009) and vertebrates (Kishida et al 2013). However, trait variation coming from previous habitats is typically neglected in spatial models of competitive coexistence (HilleRisLambers et al 2012).…”
Section: Carry-over Effects and Species Interactionsmentioning
confidence: 99%
“…Trait variation in response to present environmental cues (e.g. development of anti-predator morphologies or nutrient stress) frequently affects interactions between diverse taxa such as plants and herbivores (terHorst & Lau 2012), protists (DeLong, Hanley & Vasseur 2013), invertebrates (Hoverman & Relyea 2009) and vertebrates (Kishida et al 2013). However, trait variation coming from previous habitats is typically neglected in spatial models of competitive coexistence (HilleRisLambers et al 2012).…”
Section: Carry-over Effects and Species Interactionsmentioning
confidence: 99%
“…Although past studies have evaluated the effects of cannibalism on the abundance of heterospecific prey , Rudolf 2006, Law and Rosenheim 2011, they did not examine how cannibalism affects the phenotypic characteristics of the two populations. We expect that, by exploring the consequences of cannibalism on the phenotypic characteristics of predator and prey populations, we will gain insight into the ecological consequences of cannibalism, because phenotypic traits such as behavior, life history, and morphology of key species influence both ecological interactions and trait evolution in a community (Agrawal 2001, Werner and Peacor 2003, Miner et al 2005, Takatsu and Kishida 2013, Kishida et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…A). Since salamander larvae with the offensive morph consume more frog tadpoles than those with the non‐offensive morph even if their canonical size (body size) is similar (Takatsu and Kishida , Kishida et al ), we can infer that the allometric growth due to the inducible offence itself contributed to the predation success of the early‐hatched salamander larvae in this experiment, independently of ordinary growth. Inducible offences are widespread among predator taxa (reviewed by Kishida et al ) and theory suggests that the evolution of inducible offences is part of an adaptive phenotypic plasticity strategy of predators to overcome the inducible defences of their prey (Mougi et al ).…”
Section: Discussionmentioning
confidence: 74%
“…Diff erential eff ects on life-history traits among the treatments could refl ect diff erences in predation pressure among them. Th e results of a recent fi eld study (Kishida et al 2014), in which the presence or absence of off ensive and non-off ensive morphs of salamander larvae were experimentally manipulated, support this possibility. Kishida et al (2014) showed that the frog tadpoles were larger at metamorphosis and they metamorphosed later when they were exposed to stronger predation pressures from off ensivemorph salamander larvae.…”
Section: Discussionmentioning
confidence: 93%